تصوف و اصطلاحاتِ تصوف کی بنیادیں قرآن و سنت میں ؛ایک تجزیاتی مطالعہ: Sufism and the foundations of Sufism in the Qur’an and Sunnah: An Analytical Study - Bilal, Haris; Yaseen, Ms. Farhat (Al-Amīr Research Journal for Islamic Studies, 2023)
Sufism is an expression of the aesthetics of Muslim civilization. It makes right acceptable and good worthy of action and makes them attractive to human feeling. When this knowledge and art became organized in the Muslim academic discourse, it remained in the stages of editing and completion for centuries. Many people with high consciousness cultivated this art. And it was served by the power of different linguistic crosses. The Indo-Muslim tradition has an unusual expression in Islamic history in this respect. Sufis in the subcontinent introduced many people to Islam through Sufism and played their role in popularizing Islam. When Sufism became a formal knowledge and the Sufis started working to promote it, the question arose in many minds as to whether or not there is any evidence or basis for Sufism from the Qur’an and Sunnah. The answer to the same question has been sought in this paper. The article under review discusses some academic terms of the Muslim mystical tradition in the light of the teachings of Qur’an and Hadith. Key Words: Qur’an, Hadith, Sufism, Sub-Continent, Karamat, Kashf, Ilham.